2010
DOI: 10.1097/qai.0b013e3181c7d72f
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV and STIs and Associated Risk Factors Among Female Sex Workers in Guangdong Province, China

Abstract: Objectives To assess the prevalence of human immunodeficiency virus (HIV) and sexually transmitted infections (STIs) and associated factors among female sex workers (FSWs) in Guangdong, China. Methods Respondent driven sampling was used to recruit 320 FSWs. The recruited participants were interviewed face-to-face using a structured questionnaire and tested for HIV, syphilis, gonorrhea, and Chlamydia. Results The prevalence of syphilis, gonorrhea, and Chlamydia were 8.0% (4.6-12.2%), 9.5% (5.6-14.3%) and 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 13 publications
3
39
0
2
Order By: Relevance
“…A majority of studies were conducted in South China (Guangdong, Guangxi, Hainan, Hunan), Southwest China (Guizhou, Sichuan, Yunnan), or large urban cities (e.g., Beijing, Shanghai, Wuhan, Zhengzhou, and others). Between 13% and 90.6% (median 041.5%) of FSW were diagnosed or tested positive for at least one STI (Chen et al, 2005;Chen et al, 2008;Gil et al, 1996;Lau, Tsui, Siah, & Zhang, 2002;Li et al, 2006;Li et al, 2010;Ruan et al, 2006;B. Wang et al, 2005B.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A majority of studies were conducted in South China (Guangdong, Guangxi, Hainan, Hunan), Southwest China (Guizhou, Sichuan, Yunnan), or large urban cities (e.g., Beijing, Shanghai, Wuhan, Zhengzhou, and others). Between 13% and 90.6% (median 041.5%) of FSW were diagnosed or tested positive for at least one STI (Chen et al, 2005;Chen et al, 2008;Gil et al, 1996;Lau, Tsui, Siah, & Zhang, 2002;Li et al, 2006;Li et al, 2010;Ruan et al, 2006;B. Wang et al, 2005B.…”
Section: Resultsmentioning
confidence: 96%
“…The estimated two to four million female sex workers (FSW) comprise a highly heterogeneous population that includes those from both lower end (i.e., streets, beauty salons, roadside motels, and temporary sublets) and higher end venues (i.e., karaoke clubs, massage parlors, night clubs, and hotels) (Ding et al, 2005;Huang, Henderson, Pan, & Cohen, 2004;Li et al, 2010;Ruan et al, 2006;Wang et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…In 2009 it reported 39 112 syphilis cases and prevalence reached 41 cases per 100 000 total population, or nearly twice the rate in all of China (25 per 100 000). 6 Syphilis is now the second most commonly reported communicable disease in Guangdong province, 6 where a high prevalence has been observed among female sex workers 7 and men who have sex with men. 8,9 Mother-to-child syphilis transmission is an important public concern in epidemic areas because syphilis can cause spontaneous abortion, stillbirth and irreversible congenital defects.…”
Section: Introductionmentioning
confidence: 99%
“…Chlamydia prevalence in FSWs varied from 3% to 46% [9-12, 15, 16] and was highest in some studies in Yunnan Province [8,9]. Finally, syphilis prevalence was higher than in Shanghai in almost all other studies examined, from 3% to 16% [8][9][10][11][12][13][16][17][18][19][20][21][22][23][24]. Interestingly, a repeated cross-sectional study from neighbouring Zhejiang found a marked decrease in syphilis prevalence over the four years examined: 2006, 13·5%; 2007, 0·8%; 2008, 0·0%; 2009, 0·5% [24], and found no HIV infections and a syphilis prevalence of 4·5%.…”
Section: Discussionmentioning
confidence: 98%